Fenomena Demotivasi Belajar Bahasa Arab di Indonesia - Ramli, Ramli (Universitas Islam Ahmad Dahlan Sinjai, 2025)
Arabic Language is the oldest foreign language (second language) known and studied by the Indonesian people. Arabic was known and studied in Indonesia long before other foreign languages ​​such as English, German, and Mandarin. In the 1980s, Arabic was the favorite language for students in Indonesia. However, over time, the love and enthusiasm for learning Arabic in Indonesia has decreased. This phenomenon is called the